EFEKTIFITAS PENGETAHUAN AWAL (PRIOR KNOWLEDGE) DALAM PENGAJARAN MEMBACA (READING) BAHASA INGGRIS. - Hadi Sumarto (Alm) (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
Reading is  a  complex cognitive  process of  decoding symbols in  order  to  construct  or  derive meaning (reading comprehension). It is a means of language acquisition, of communication, and of sharing information and ideas. Like all language, it is a complex interaction between the  text  and  the  reader  which  is  shaped  by  the  reader’s  prior  knowledge,  experiences, attitude,  and  language  community  which  is  culturally  and  socially  situated.  The  reading process requires continuous practice, development, and refinement. Key words: cognitive process, prior knowledge, complex interaction between the text and the reader